2020
DOI: 10.3991/ijet.v15i21.15933
|View full text |Cite
|
Sign up to set email alerts
|

Students' Project Competency within the Framework of STEM Education

Abstract: The article is devoted to formation of students' project competence within the framework of STEM education. Project competence is an important component of professional competence of a future specialist and is applicable to designate professionalism. The article identifies the main characteristics of STEM education as means of formation of project competence of students. Project competence is characterized by possession of special knowledge, skills and abilities (to solve problems on the basis of putting forwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…In addition, Nouri et al (2017) also explain that collaborative learning can effectively solve problems and improve students' ability to complete projects. Collaborative learning also requires project competence, meaning that students have special knowledge, skills and abilities to solve problems based on hypotheses, set activity goals, plan activities, collect and analyse required information, conduct experiments and present research results (Levanova et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Nouri et al (2017) also explain that collaborative learning can effectively solve problems and improve students' ability to complete projects. Collaborative learning also requires project competence, meaning that students have special knowledge, skills and abilities to solve problems based on hypotheses, set activity goals, plan activities, collect and analyse required information, conduct experiments and present research results (Levanova et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In this literature review, there are five studies related to performance-based assessment, namely [43][44][45][46][47]. In the formative assessment approach, there are three studies, namely [48][49][50]. The rest are studies using a variety of assessment approach terms, namely, criteria-based assessment [51], e-portfolio assessment [52], school-based assessment [53], summative assessment [54], workplace assessment [55], computer-based assessment [56], scenario-based assessment [57], inclusive-based assessment [58], and classroom-based assessment [59].…”
Section: Assessment Approaches Used To Assess Students In Technical A...mentioning
confidence: 99%
“…It is expressed by possessing knowledge, skills, and exceptional knowledge abilities. The authors of [48] found that assessment methods included operational feedback, continuous quality assessment for each completed practical, and criteria-based assessment.…”
Section: Formative Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The practices carried out in this phase of the study were programming Dojo (with the Scratch tool, similar at [37]) and the Java language; the practical project, as indicated [38], divided into two parts. Further details will be provided later, in the Execution section.…”
Section: Phase Iv: Practical and Collaborative Activitiesmentioning
confidence: 99%